Pengaruh Kinerja Keuangan terhadap Kepemilikan Asing dengan Moderasi Ukuran Perusahaan pada Perusahaan Non-Keuangan di Bursa Efek Indonesia - Suhartin Mohamad Syarif; Gabriel Tanusi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Foreign ownership represents an important indicator of international investors' confidence in a company's prospects and financial performance. Inconsistent findings in previous studies regarding the determinants of foreign ownership highlight the need for a more comprehensive analysis by incorporating firm characteristics as a moderating variable. A quantitative approach was employed using panel data from non-financial companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample consisted of 30 companies selected through purposive sampling. Panel data regression with the Fixed Effect Model (FEM) was applied to examine the effects of profitability, liquidity, and leverage on foreign ownership while evaluating the moderating role of firm size. The empirical results reveal that profitability has a negative and significant effect on foreign ownership, whereas liquidity and leverage have positive and significant effects. Simultaneously, all independent variables significantly influence foreign ownership. The moderation analysis demonstrates that firm size strengthens the relationship between profitability and foreign ownership but weakens the effects of liquidity and leverage. These findings contribute to the literature on foreign ownership determinants by providing empirical evidence that both financial performance and firm characteristics shape foreign investors' investment decisions. The results also offer practical insights for corporate managers in improving investment attractiveness through effective financial performance management while considering the strategic role of firm size.